Enhancing adolescent health: the role of strength and endurance school-based HIIT interventions in physical fitness and cognitive development - Pérez-Ramírez, José Antonio; Santos, Maria Paula; Mota, Jorge; González-Fernández, Francisco Tomás; Villa-González, Emilio (Frontiers in Psychology, 2025)
IntroductionPhysical activity (PA) is widely known for its outstanding benefits across several health domains including physical, psychological, social, and cognitive in children and adolescents. However, global trends indicate how low levels of PA and physical fitness among adolescents are increasing, with over 80% failing to meet the World Health Organization (WHO) guidelines of 60 min of moderate-to-vigorous physical activity (MVPA) daily.MethodsThis study aimed to evaluate the effects of an 8-week high-intensity interval training (HIIT) intervention based on strength and endurance trainings protocols during physical education (PE) classes on body composition, physical fitness, and cognitive functions in adolescents aged 13–17 years. A quasi-experimental pre-post design was employed with experimental group (EG) and control group (CG).ResultsResults indicated significant improvements in the EG in cardiorespiratory fitness (VO2max), strength (hand grip, horizontal jump), and speed-agility (4 × 10 m test). Cognitive outcomes assessed via the D2 attention test revealed notable enhancements in concentration, a reduction in errors, and improved processing speed in the EG relative to the CG (p > 0.05).DiscussionFuture studies should explore the long-term impacts of HIIT on cognitive growth and academic achievement, as well as determine the ideal duration and frequency of sessions to optimize benefits in various educational contexts. The results obtained reinforce the use of HIIT in school environments and are further research on its application.